ʻAnāṣir-i dāstānī wa namāyišī dar mīrāṯ-i adabīyāt-i fārsī - Ḥanīf, Muḥammad (Intišārāt-i ʻIlmī wa Farhangī, 2020)
1. Fiction – Authorship. 2. Fiction – Stories, plots, etc. 3. Narration (Rhetoric). 4. Playwriting
Literaturverzeichnis Seit 389-399
Keywords: Fiction / Authorship; Fiction / Stories; plots; etc; Narration (Rhetoric); Playwriting; Fiction; Fiction; Authorship; Stories; plots; etc; Literatur; Erzähltechnik; Fiktion; Persisch